Anti-Inflammatory And Anti-Oxidant Activities Of Glochidion Daltonii Branch Extract - Jintana Junlatat; Bungorn Sripanidkulchai (Universitas Airlangga, 2016)
Background: Glochidion daltonii (Míœll. Arg.) Kurz, Euphorbiaceae family, is a native medicinal plant in tropical regions of Asia. In Thailand, it has traditionally been used for treating pain and mouth inflammation. Objective: This study aims to investigate the anti-inflammatory and anti-oxidant effects of G. daltonii ethanolic extract (GDE) both in vitro and in vivo. Method: The anti-inflammatory mechanism was examined in E.coli LPS-stimulated RAW264.7 cells by using semi-quantitative-reverse transcription-polymerase chain reaction and the potential anti-inflammatory effect of GDE was evaluated in Sprague-Dawley rat using carrageenan-induced rat paw edema method. In addition, DPPH assay was used for anti-oxidant evaluation. Result: The results showed that GDE at 0.063 - 0.250 mg/mL concentrations inhibited the expressions of tumor necrosis factor-α and interleukin-1β. Moreover, an intraperitoneal administration of GDE significantly reduced paw edema in rats. Furthermore, GDE showed high anti-oxidant property with IC50 values at 6.35 ± 0.28 µg/mL. Conclusion: The results support the traditionally use of GDE for treating inflammation.